From Policy to Practice: Implementing One Health Approach in Public Health in India - Krishna M. Jasani; Sanjay Gupta (NMO Journal)
The One Health approach, which integrates human, domestic animal and environmental health, is becoming an essential paradigm for tackling multifaceted public health issues. An important aspect of One Health is improving interaction and collaboration among different stakeholders not only at international and national levels but also at local levels. This is particularly relevant in India, where a major proportion of the population lives in rural areas and has deep-rooted daily contact with domestic as well as wild animals. In the case of India, where there is a great risk of zoonotic diseases, antimicrobial resistance and environmental destruction, the application of One Health is both necessary and difficult. This review analyses India’s policy gaps, practical frameworks and the challenges of adopting One Health focusing on the transformative potential of public health endeavours.